2019
DOI: 10.1039/c8tc04631j
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced multi-directional deformation of azobenzene molecular crystals

Abstract: Photoinduced multi-directional deformation of azobenzene molecular crystals enabled by photoisomerization and photothermal effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 42 publications
0
40
0
2
Order By: Relevance
“…They attribute these photoinduced multi-directional motions to the volume change of the irradiated crystal surface at different temperatures. [42] This work demonstrated that the competition between photoisomerization and photothermal effects could affect the direction of motion under illumination.…”
Section: Reviewsmentioning
confidence: 80%
See 2 more Smart Citations
“…They attribute these photoinduced multi-directional motions to the volume change of the irradiated crystal surface at different temperatures. [42] This work demonstrated that the competition between photoisomerization and photothermal effects could affect the direction of motion under illumination.…”
Section: Reviewsmentioning
confidence: 80%
“…Very recently,Hao et al investigated photoinduced multidirectional deformations of plate-like crystals of 4-cyano-4'pentyloxy azobenzene (31;F igure 17 a). [42] The T m of trans-31 was 108 8 8Cw hile that of the cis-31 was 74-83 8 8C ( Figure 17 b,c). Since the T m gap between the two isomers is large,the temperature for photomechanical study was divided into two regions:1)below the T m of cis-31,both trans-and cismolecules are solid, and 2) above the T m of cis-31 but below the T m of trans-31, cis-31 is liquid and trans-31 remains solid.…”
Section: Reviewsmentioning
confidence: 95%
See 1 more Smart Citation
“…Upon thermally induced crystallization to the E isomer energy in form of heat (97.1 kJ mol −1 ) is released, which is almost twice the conformational energy difference between the E and Z isomers (50 kJ mol −1 ) and provides a possible path to thermal energy storage. By setting the ambient temperature below, above, or near the melting temperature of the Z isomer of an AB crystal, multidirectional deformations could be achieved as the light‐induced change in volume within the crystal significantly depends on the aggregation state of both isomers . Besides, photochromic molecules theoretically have more than one crystallization pattern based on the isomer of the photoswitchable moieties.…”
Section: Crystalline Photoswitchable Materialsmentioning
confidence: 99%
“…In the early 2000s, photomechanical effects in dry polymer systems were significantly enhanced by the application of crosslinked liquid‐crystalline polymers (CLCPs). The success in realizing various 3D motions with CLCPs stimulated the development of other photomechanical systems such as nanocomposites, organic crystals, and supramolecules …”
Section: Introductionmentioning
confidence: 99%